PENGEMBANGAN MEDIA AUDIO VISUAL PADA MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MATA PELAJARAN GARDU INDUK (GI) KELAS XI TJTL SMK - Yosanda, Dwi Putri; ., Baharuddin (JEVTE Journal of Electrical Vocational Teacher Education, 2023)
Abstract This research aims to: (1) Find out how to develop audio visuals in the Discovery Learning Learning Model for the Main Substation (GI) Subject at SMK Negeri 1 Percut Sei Tuan. (2) Knowing the feasibility of Audio Visual in the Discovery Learning learning model developed for students of SMK Negeri 1 Percut Sei Tuan. (3) Knowing students' responses to Audio Visual in the Discovery Learning model developed for students of SMK Negeri 1 Percut Sei Tuan. This research will be tested involving class This type of research is Research and Development (R&D) with the ADDIE research model. The ADDIE research model includes 5 stages, namely first analysis which includes product needs analysis, second design, namely compiling an outline, layout and Audio Visual material, third development, namely developing a product that has been designed for validation in order to get input by media experts and material experts. The fourth implementation is implementing the product to get a response from users (Students) to the Audio Visual that has been developed. The fifth evaluation is evaluating Audio Visual based on several inputs from experts and user responses. The instruments used in this research were a validation questionnaire and a user response questionnaire. The results of this research are known: (1) This development research produces a product in the form of Audio Visual in the Discovery Learning learning model. (2) The feasibility of this Audio Visual was obtained from the results of material expert validation in the "Very Eligible" category which obtained an average score of 3.7. And the next validation results were obtained from media experts in the "Very Appropriate" category who received an average score of 3.6. (3) The results of user responses to this Audio Visual were categorized as "Very Good" which obtained an average score of 3.6 for students in small groups, 3.6 for students in large groups. The recommendation in this research is that Audio Visual in learning activities should be further developed in other subjects so that it can increase students' motivation and enthusiasm for learning.. Key Words: Audio Visual, Discovery Learning, Substation AbstrakPenelitian ini bertujuan untuk : (1) Mengetahui cara mengembangkan Audio Visual Pada Model Pembelajaran Discovery Learning Untuk Mata Pelajaran Gardu Induk (GI) SMK Negeri 1 Percut Sei Tuan. (2) Mengetahui kelayakan Audio Visual pada model pembelajaran Discovery Learning yang dikembangkan untuk siswa SMK  Negeri 1 Percut Sei Tuan. (3) Mengetahui respon siswa terhadap Audio Visual pada model pembelajaran Discovery Learning yang dikembangkan untuk siswa SMK  Negeri 1 Percut Sei Tuan. Penelitian ini akan diuji coba dengan melibatkan siswa kelas XI Teknik Jaringan Tenaga Listrik SMK Negeri 1 Percut Sei Tuan semester ganjil tahun ajaran 2022/2023. Jenis penelitian ini adalah Research and Development (R&D) dengan model penelitian ADDIE. Model penelitian ADDIE meliputi 5 tahapan yaitu pertama analysis yang meliputi analisis kebutuhan produk, kedua design yaitu menyusun garis besar, layout dan materi Audio Visual, Ketiga development yaitu mengembangkan produk yang sudah didesain untuk dilakukan validasi agar mendapatkan masukan oleh ahli media dan ahli materi. Keempat implementation yaitu menerapkan produk untuk mendapatkan respon dari pengguna (Siswa) terhadap Audio Visual yang telah dikembangkan. Kelima evaluation yaitu mengevaluasi Audio Visual berdasarkan beberapa masukkan dari para ahli serta respon pengguna. Instrumen yang digunakan pada penelitian ini adalah angket validasi dan angket respon pengguna. Hasil Penelitian ini diketahui : (1) Penelitian pengembangan ini menghasilkan produk berupa Audio Visual pada model pembelajaran discovery learning. (2) Kelayakan Audio Visual ini didapatkan dari hasil validasi ahli materi dengan kategori œSangat Layak yang memperoleh nilai rata-rata sebesar 3,7. Dan hasil validasi berikutnya didapatkan dari ahli media dengan kategori œSangat Layak yang memperoleh nilai rata-rata sebesar 3,6. (3) Hasil respon pengguna terhadap Audio Visual ini dikategorikan œSangat Baik yang memperoleh nilai rata-rata sebesar 3,6 pasa siswa dalam kelompok kecil, 3,6 pada siswa dalam kelompok besar. Rekomendasi pada penelitian ini adalah Audio Visual dalam kegiatan pembelajaran harus lebih dikembangkan lagi pada mata pelajaran lainnya sehingga dapat meningkatkan motivasi dan semangat belajar siswa.Kata kunci : Audio Visual, Discovery Learning, Gardu Induk